2018
DOI: 10.1212/wnl.0000000000006396
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with Parkinson disease psychosis receiving pimavanserin and quetiapine

Abstract: Parkinson disease (PD) is a complex neurodegenerative disorder. Cognitive dysfunction and psychosis are leading contributors to nursing home placement. 1 Psychosis onset is associated with cognitive decline, levodopa supplementation, and visual dysfunction. 2 Treatment of PD psychosis (PDP) centers on levodopa dose adjustment, use of second-generation antipsychotics (SGAs), and cholinesterase inhibitors. SGAs function via serotonergic modulation and dopamine receptors blockade. Quetiapine, a structural analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…As noted, we did not see increased mortality rates in the group that started pimavanserin compared to those who did not start the medication. There has been recent discussion on whether patients taking pimavanserin carry a higher mortality risk [ 25 ], and our real-world data does not support this assertion, in keeping with other real-world reports [ 11 ]. However, this retrospective study was not powered to make claims on mortality risk with pimavanserin, and we report our clinical findings with this important caveat.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As noted, we did not see increased mortality rates in the group that started pimavanserin compared to those who did not start the medication. There has been recent discussion on whether patients taking pimavanserin carry a higher mortality risk [ 25 ], and our real-world data does not support this assertion, in keeping with other real-world reports [ 11 ]. However, this retrospective study was not powered to make claims on mortality risk with pimavanserin, and we report our clinical findings with this important caveat.…”
Section: Discussionsupporting
confidence: 68%
“…To date, reports of real-world experience with pimavanserin have been limited by small sample sizes ( n = 2 and 15) [ 9 , 10 ] or limited scope [ 11 ], preventing a meaningful analysis of real-world efficacy and patient characteristics, including PD or DLB diagnosis, presence and severity of dementia, deep brain stimulation (DBS) use, and prior antipsychotic failure. In this retrospective chart review, we sought to evaluate the clinical efficacy of pimavanserin in a larger cohort and describe prescribing patterns, concomitant antipsychotic use, titration strategies, and tolerability in patients with various clinical presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, preliminary research has shown an increased risk of mortality and morbidity with antipsychotic use in PD patients, too, and not specific to dementia . Additional controlled research is needed to determine if antipsychotics increase mortality risk in PD and if pimavanserin is similar to other antipsychotics in this regard . Moreover, rivastigmine may be another treatment option for psychotic behavior specifically in patients with PD and dementia based on a post hoc analysis of a large, placebo‐controlled study of rivastigmine in PD dementia that showed improvement of hallucinations on rivastigmine …”
Section: Discussionmentioning
confidence: 99%
“…143,144 Additional controlled research is needed to determine if antipsychotics increase mortality risk in PD and if pimavanserin is similar to other antipsychotics in this regard. 145 Moreover, rivastigmine may be another treatment option for psychotic behavior specifically in patients with PD and dementia based on a post hoc analysis of a large, placebo-controlled study of rivastigmine in PD dementia that showed improvement of hallucinations on rivastigmine. 146 It is critical for PD patients to be monitored closely for the development of ICRDs as part of routine clinical care, which ideally would include caregiver reports, because ICRDs may have potentially devastating psychological, social, legal, and economic consequences, including divorce, bankruptcy, incarceration, and attempted suicide.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Initial concerns of higher rates of mortality were shown to be no higher than those in this already frail patient group. 27 …”
Section: Mechanismsmentioning
confidence: 99%